Genomics-Assisted Crop Improvement
DOI: 10.1007/978-1-4020-6297-1_11
|View full text |Cite
|
Sign up to set email alerts
|

Genomics Approaches To Soybean Improvement

Abstract: Abstract:Soybean, Glycine max (L.) Merr., has become the major source of edible vegetable oils and high protein feeds for livestocks in the world. A native of Eastern Asia, soybean was introduced into the USA and South America where it has become the most economically important agricultural crop and export commodity. In recent years, as demand for soybean increased due to the values of seed oil and protein, as well as industrial and nutriceutical uses, it has received more attention by scientists aiming to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 167 publications
0
9
0
Order By: Relevance
“…Over 61 QTLs are associated with the protein content in 17 different soybean populations (Vuong et al, 2007). The seed composition traits may be associated with seed sucrose content in soybean and a QTL for seed sucrose content on Chr 20 made a phenotypic contribution of greater than 10%, which may be a major QTL with a pleiotropic effect (Maughan et al, 2000).…”
Section: Qtls For Seed Protein/oil Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Over 61 QTLs are associated with the protein content in 17 different soybean populations (Vuong et al, 2007). The seed composition traits may be associated with seed sucrose content in soybean and a QTL for seed sucrose content on Chr 20 made a phenotypic contribution of greater than 10%, which may be a major QTL with a pleiotropic effect (Maughan et al, 2000).…”
Section: Qtls For Seed Protein/oil Contentmentioning
confidence: 99%
“…Since soybean [ Glycine max (L.) Merrill] seed is a good source of protein and oil, it is grown widely throughout the world for its numerous uses, such as various edible products, animal feed and potential industrial applications (Vuong et al, 2007; Van et al, 2008; Kim et al, 2012). Although the wild soybean ( G. soja Sieb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these interfered in QTLs to improve protein and oil content of soybean by marker-assisted selection (MAS). On the other hand, several studies reported SNP markers associated with QTL for several traits in soybean (Vuong, Wu, Pathan, Valliodan, & Nguyen, 2007), but there are only two studies reported an exclusively SNP-based genetic map (Kassem, 2012;Hyten et al, 2010a). The genetic relationship between moisture, protein, oil and other traits could be explored by comparing QTL mapping results when available and fine mapping of each trait would provide accurate genetic information.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean (Glycine max), an economical legume crop, is one of alternative source of protein (Hanafie, 2004;Vuong et al, 2007). In the last 20 years, Indonesian soybean plantations showed significant decreases both in total areas and production with a total national area of 1.6 millions ha and total production of 1.87 million tons in 1992 to become only 0.551 million ha and 0.780 million tons in 2013.…”
Section: Introductionmentioning
confidence: 99%